Callus induction of cottoni seaweed (Kappaphycus alvarezii (Doty) Doty) collected from Natuna Islands, Riau Islands Province. - Erina Sulistiani (Biotropia: The Southeast Asian Journal of Tropical Biology, 2013)
The objective of this study was to obtain the optimal medium for callus induction from thallus explants of  Kappaphycus alvarezii (Doty) Doty. Before cultured,  Cottonii seaweeds collected from the Natuna Islands (Riau Islands Province) were acclimatized in greenhouse and in semi-sterile culture in the laboratory. Sterilized explants were cultured on PES and CW media solidified with 0.8% Bacto agar. In each of these media were added two combinations of plant growth re gulators i.e. BAP+IAA and BAP+NAA. The concentrations of BAP used were 0, 0.5, 1 mg/l, the concentrations of IAA were 0, 2.5, 5 mg/l, whereas the concentration of NAA were 0,  0.5, 1 mg/l. The result indicated that  the optimal medium for callus induction was PES solidified medium supplemented with BAP 1 mg/l. Types of callus formed were (a) white compact callus, (b) white filamentous callus, (c) greenish / brownish callus. Regeneration of callus into clump of filament had  been done by subcultured the callus into PES solidified medium supplemented with BAP 1 mg/l + IAA 2.5 mg/l.